2007
DOI: 10.1016/j.physleta.2006.12.067
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and neutron diffraction studies of coupled structural phase transitions in DyBaCo2O5.5

Abstract: A structural transition at T ≈ 322 K from the P mmm to P mma phase is found to coincide with an anomaly of resistivity. Another structural phase transition doubling the lattice parameter c, which has been postulated earlier to accompany a low-temperature magnetic transition in TbBaCo2O5.5, is observed in a single crystal DbBaCo2O5.5 by means of the X-ray and neutron diffraction. The low temperature phase does not belong to the space group P cca that has been chosen earlier as the highest subgroup of the P mma.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
6
12
0
Order By: Relevance
“…This indicates that the single crystal does not undergo phase separation below T L and has Bmmm symmetry, thus confirming the relevance of polycrystallinity and microstructural factors. It should be noted that the weak nuclear reflections ͑h ,0,l +0,k , l; h / k, l =2n +1͒ observed by Chernenkov et al 14 on the twinned DyBaCo 2 O 5.5 single crystal by x-ray diffraction are consistent with the model proposed in this work, since Bmmm space group allows the presence of ͑h ,0,l͒ reflections with h + l =2n. Moreover, since there is no group-subgroup relationship between the Pmma and Bmmm space groups, the corresponding phase transition should be of the first order, again in agreement with the diffraction experiments.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…This indicates that the single crystal does not undergo phase separation below T L and has Bmmm symmetry, thus confirming the relevance of polycrystallinity and microstructural factors. It should be noted that the weak nuclear reflections ͑h ,0,l +0,k , l; h / k, l =2n +1͒ observed by Chernenkov et al 14 on the twinned DyBaCo 2 O 5.5 single crystal by x-ray diffraction are consistent with the model proposed in this work, since Bmmm space group allows the presence of ͑h ,0,l͒ reflections with h + l =2n. Moreover, since there is no group-subgroup relationship between the Pmma and Bmmm space groups, the corresponding phase transition should be of the first order, again in agreement with the diffraction experiments.…”
supporting
confidence: 91%
“…The conclusion that below T L the high temperature polymorph ͑Pmma with the k = c * / 2 magnetic wave vector͒ coexists with the new phase ͑Bmmm with k =0͒ is in concurrence with recent work by Chernenkov et al 14 The single- FIG. 4.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The determination of the space group of the magnetically ordered RBaCo 2 O 5.5 compounds is difficult, and it has recently been shown that DyBaCo 2 O 5.5 in contrast to TbBaCo 2 O 5.5 does not transform to a low-temperature phase with Pcca symmetry. 21 The Pmma space group was therefore retained for the chemical structure of HoBaCo 2 O 5.5 for T ഛ 265 K in the present study. The atomic coordinates were fixed at the values obtained at 275 K, and only lattice parameters and thermal displacement parameters were refined for T ഛ 265 K. This approximation to the chemical structure below 265 K was made to reduce the number of refineable structural parameters.…”
Section: Resultsmentioning
confidence: 99%
“…3, [13]). A huge temperature hysteresis of about 100 K is observed for the X-ray intensities of both the superstructure and basic Bragg reflections [18].…”
Section: Neutron and X-ray Diffraction Studies Of Dybaco 22 O 55mentioning
confidence: 99%